Espécies nativas do componente arbustivo para uso na fase inicial da restauração florestal - Souza, Alessandra Nascimento (2023)
The unsustainable exploitation of forests has leveraged the fragmentation and loss of habitats, generating serious impacts on biodiversity, with the recovery of these areas being a relevant issue to re-establish an ecologically balanced environment. In this process, finding native species with potential for growth, shading and competition with grasses is paramount to assist in the process of ecological restoration. Two experiments were carried out with the species Vernonia polyanthes, Solanum paniculatum, Baccharis dracunculifolia and Solanum lycocarpum in order to generate information about the potential use of these shrub species in the initial stage of forest restoration. In the study carried out in chapter 1, the development of plants in pots was evaluated, under controlled humidity conditions and the design was in randomized blocks, being 5 blocks, 3 treatments (substrates for growth) with evaluation distributed in time. Plant growth was evaluated monthly, for 7 months, using the variables height and stem diameter. Subsequently, the determination of the dry mass was carried out. The four species studied have the potential to develop in soils without ideal planting conditions, however, fertilization proved to be an important factor for better plant development, especially in the growth of the collar diameter, which is an important variable for the establishment of plants in the field. In chapter 2, to evaluate the seedling production process, the experimental design was in randomized blocks with four replications and 24 plants per plot, with treatments arranged in a 3 x 2 factorial scheme. Three substrate compositions were evaluated in two volumes of tubes (55 cm³) and (110 cm³) and the quality and growth of the seedlings were evaluated using the variables height and diameter of the stem at 60, 90 and 120 days after sowing. At 120 days, the dry mass was evaluated. Seedlings of the four species studied can be produced in a nursery, using any of the substrates and tubes studied for S. paniculatum and substrate 3 is recommended (20% commercial substrate (Maxfertil); 30% coconut fiber; 20% carbonized rice husk; 30% tanned bovine manure and 3kg/m³ of Osmocote fertilizer) for B. Dracunculifolia, substrate 2 for V. polyanthes (35% commercial substrate (Maxfertil); 30% coconut fiber; 20% carbonized rice husk; 15% tanned bovine manure and 3kg/m³ of Osmocote fertilizer) and substrate 1 (50% commercial substrate (Maxfertil); 30% coconut fiber; 20 % of carbonized rice husk and 3kg/m³ of Osmocote fertilizer) for the species S. lycocarpum due to the higher values achieved. The species showed relevance due to their rapid growth and vigor of their individuals, demonstrating potential for use in the forest restoration process.